Historicist interpretation of the Olivet Discourse and the sixth seal 1. Medieval tribulation and cosmic signs - Charlesworth, Scott D. (2017)
Historicist interpreters of the Olivet Discourse turn Mark 13:4 par. into a two-part question about (1) the destruction of the temple and (2) the signs heralding the parousia. In doing so they attempt to: (1) solve the crux of 13:30 par. by relating 'this generation' to the events of 70 ce; (2) read a medieval persecution into 13:19-20 par.; and (3) find parallel historical fulfilments for the cosmic signs in the Olivet Discourse and sixth seal of the Apocalypse. While the general sweep of the Olivet Discourse up to the parousia is not in question, the apocalyptic Jesus of the synoptic gospels taught that the destruction of Jerusalem would usher in signs in the heavens and then the parousia. Indeed, according to Matthean redaction of Mark, the greatest tribulation of all time would occur in connection with the destruction of Jerusalem and 'immediately' be followed by cosmic signs and the glorious return of Jesus Christ (24:29-30). Consequently, a reference to medieval tribulation in the Olivet Discourse is highly improbable, as is identification of the cosmic signs in the Olivet Discourse and the sixth seal with historical events in the 18th and 19th centuries.
Keywords: Apocalypse; Olivet Discourse; cosmic signs; Historicism; medieval tribulation; sixth seal